Combined role of molecular diffusion, mean streaming and helicity in the eddy diffusivity of short-correlated random flows. (19th October 2016) - Martins Afonso, Marco; Mazzino, Andrea; Gama, Sílvio
Abstract: We analytically investigate the effective-diffusivity tensor of a tracer particle in a fluid flow endowed with a short correlation time. By means of functional calculus and a multiscale expansion, we write down the main contributions to the eddy diffusivity due to each single physical effect and to their interplays. Namely, besides molecular diffusivity and a constant uniform mean streaming, we take into account the possibility for the (incompressible, Gaussian, stationary, homogeneous, isotropic) turbulent fluctuations to break parity invariance. With respect to the classical turbulence-driven diffusivity amplification for delta-correlated flows, we find that the presence of a short temporal correlation induces a diminution even when coupled with such effects, with two principal exceptions. Notably, the diffusivity is—perturbatively—enlarged not only by the helical contribution itself, but also by the interference between molecular diffusion and mean flow.